PEGylated Human Serum Albumin: Review of PEGylation, Purification and Characterization Methods - Parvin Akbarzadehlaleh; Mona Mirzaei; Mahdiyeh Mashahdi-Keshtiban; Karim Shamsasenjan; Hamidreza Heydari (Tabriz University of Medical Sciences, 2016)
Human serum albumin (HSA) is a non-glycosylated, negatively charged protein (Mw: about 65-kDa) that has one free cystein residue (Cys 34), and 17 disulfide bridges that these bridges have main role in its stability and longer biological life-time (15 to 19 days). As HSA is a multifunctional protein, it can also bind to other molecules and ions in addition to its role in maintaining colloidal osmotic pressure (COP) in various diseases. In critical illnesses changes in the level of albumin between the intravascular and extravascular compartments and the decrease in its serum concentration need to be compensated using exogenous albumin; but as the size of HSA is an important parameter in retention within the circulation, therefore increasing its molecular size and hydrodynamic radius of HSA by covalent attachment of poly ethylene glycol (PEG), that is known as PEGylation, provides HSA as a superior volume expander that not only can prevent the interstitial edema but also can reduce the infusion frequency. This review focuses on various PEGylation methods of HSA (solid phase and liquid phase), and compares various methods to purifiy and characterize the pegylated form.